Expression of DRD2 is increased in human pancreatic ductal adenocarcinoma and inhibitors slow tumor growth in mice - Jandaghi, Pouria; Knebel Doeberitz, Magnus von; Büchler, Markus W.; Strobel, Oliver; Hackert, Thilo; Giese, Nathalia (Gastroenterology, 2016)
Incidence of and mortality from pancreatic ductal adenocarcinoma (PDAC), the most common form of pancreatic cancer, are almost equivalent, so better treatments are needed. We studied gene expression profiles of PDACs and the functions of genes with altered expression to identify new therapeutic targets. We performed microarray analysis to analyze gene expression profiles of 195 PDAC and 41 non-tumor pancreatic tissue samples. We undertook an extensive analysis of the PDAC transcriptome by superimposing interaction networks of proteins encoded by aberrantly expressed genes over signaling pathways associated with PDAC development to identify factors that might alter regulation of these pathways during tumor progression. We performed tissue microarray analysis to verify changes in expression of candidate protein using an independent set of 152 samples (40 nontumor pancreatic tissues, 63 PDAC sections, and 49 chronic pancreatitis samples). We validated the functional relevance of the candidate molecule using RNA interference or pharmacologic inhibitors in pancreatic cancer cell lines and analyses of xenograft tumors in mice. In an analysis of 38,276 human genes and loci, we identified 1676 genes that were significantly up-regulated and 1166 genes that were significantly down-regulated in PDAC compared with nontumor pancreatic tissues. One gene that was up-regulated and associated with multiple signaling pathways that are dysregulated in PDAC was G protein subunit αi2, which has not been previously associated with PDAC. G protein subunit αi2 mediates the effects of dopamine receptor D2 (DRD2) on cyclic adenosine monophosphate signaling; PDAC tissues had a slight but significant increase in DRD2 messenger RNA. Levels of DRD2 protein were substantially increased in PDACs, compared with non-tumor tissues, in tissue microarray analyses. RNA interference knockdown of DRD2 or inhibition with pharmacologic antagonists (pimozide and haloperidol) reduced proliferation of pancreatic cancer cells, induced endoplasmic reticulum stress and apoptosis, and reduced cell migration. RNA interference knockdown of DRD2 in pancreatic tumor cells reduced growth of xenograft tumors in mice, and administration of the DRD2 inhibitor haloperidol to mice with orthotopic xenograft tumors reduced final tumor size and metastasis. In gene expression profile analysis of PDAC samples, we found the DRD2 signaling pathway to be activated. Inhibition of DRD2 in pancreatic cancer cells reduced proliferation and migration, and slowed growth of xenograft tumors in mice. DRD2 antagonists routinely used for management of schizophrenia might be tested in patients with pancreatic cancer.